Hedging Energy Security through Infrastructure Diplomacy: The Pursuit of Economic Sovereignty in Azerbaijan-Indonesia Energy Cooperation Post-COP29 - Nadila Putri Shenindita (Eduvest - Journal of Universal Studies, 2026)
In the wake of COP29 in Baku, the geopolitical landscape of energy has transitioned toward a "hybrid" cooperation model that balances fossil fuel reliability with green innovation. This study analyzes the strategic partnership between Azerbaijan and Indonesia (2024–2026), examining how infrastructure diplomacy serves as a mechanism for economic sovereignty. Amidst a 2026 global oil surplus and a 2.5 mb/d supply increase buffer, the research identifies a significant pivot toward sustainable infrastructure. The findings highlight the "Baku Legacy": a Joint Task Force on Green Energy acting as a "special vehicle" to bypass bureaucratic hurdles in the Waste-to-Energy (WtE) sector. Data validates that while the Baku-Tbilisi-Ceyhan (BTC) pipeline remains a critical artery for Indonesia’s oil stability—mitigating the $6/bbl price spikes seen in early 2026—the cooperation has expanded into "Pragmatic-Progressive" ESG standards. By integrating Neorealist and Constructivist frameworks, the paper concludes that this bilateral synergy allows both nations to hedge against global volatility and supply chain shocks. This "Middle-Power Standard" offers a balanced alternative to stringent Western mandates, securing strategic autonomy within the South-South green transition.